Hubungan Jenis Kelamin, Stress, dan Kepuasan Mahasiswa Akuntansi terhadap Pembelajaran Daring di Masa Pandemi COVID-19 - Tantri, Sakina Nusarifa; Roseline, Ceicillia Novita (E-Jurnal Akuntansi; Vol 31 No 7 (2021)DO - 10.24843/EJA.2021.v31.i07.p14, 2021)
This study is a quantitative study on student perceptions of online learning during the COVID-19 pandemic. The purpose of this study was to examine the model of the relationship between gender, Stress, and satisfaction of accounting students in Indonesia towards online learning during the COVID-19 pandemic. The method used in this quantitative research is a survey method using a sample of accounting students at several universities in Indonesia. The number of samples in this study were 84 students, obtained through a sampling technique that is purposive convenience sampling. The results of this study confirmed that only the effect of Stress on student satisfaction was found to be significant, while gender did not significantly affect Stress and satisfaction with online learning. Keywords: Gender; Stressed; Satisfaction; Online.